A utilização do multiplano no ensino de geometria para alunos do ensino fundamental com deciência visual - Silva, Hugleibson Bernardo da (2015)
In mathematics, when you can associate the concrete with the abstract, reap many fruits. Especially if in the classes are present students with visual impairment. Given the di culties encountered to teach Plane Geometry on Elementary School, this work has as its main objective to introduce the Multiplane as an alternative teaching of Plane Geometry, not only for people with visual impairment, but for all students, to improve learning as well as increase their interest on classes. The research also included a brief study on visual impairment, advances in legislation for inclusion of people with disabilities in the education system and the Braille code. Were also suggested some activities, adapted to the Multiplane.